Penelitian External Environmental Analysis Pada Perusahaan Maxim - Renalbi Renalbi (Journal Of Business, Finance, and Economics (JBFE), 2023)
This analysis aims to measure the performance of the core strategic management processes within Maxim's company. The results obtained are the negative and positive sides of implementing external environmental research. This research is motivated by how the company's performance system plays an important role in running and coordinating all company resources. Researchers also want to examine how the management strategy will be better if it is combined with the application of internal control in the company's system. The method chosen for this research is a qualitative research method with data collection techniques at the Maxim company. By implementing a strategic management program at Maxim Indonesia combined with research in the company's external and internal environment, the production process is expected to be more effective and efficient